Execution of Deed of Guarantee of Dependent Rights Due to Bad Loans - Manggala, Ferdiansyah Putra; Susanti, Dyah Ochtorina (Universitas Muhammadiyah Gresik, 2024)
The implementation of the execution of mortgage rights as collateral for a credit is still as contained in Article 26 UUHT which states that there is no statutory regulation that regulates it and there are still many obstacles faced in the process which trigger delays in protecting the interests of creditors for said mortgage rights. because the debtor as the one who gave the mortgage questioned or questioned the amount and the debt guaranteed by the mortgage, based on this it was what resulted in delays in the execution of the mortgage and the existence of legal incompetence in the execution. The formulation of the problem in this article is whether the creditor can immediately execute the Mortgage Guarantee Deed in the event of bad credit. The research method used is normative juridical research (Legal Research). The results of the study show that the execution of the mortgage deed cannot be carried out directly by the creditor when bad credit occurs due to the inconsistency of Article 224 HIR with Article 6 UUHT which results in execution having to be based on a court request.